Anatoxins from benthic cyanobacteria responsible for dog mortalities in New Brunswick, Canada. (May 2023) - McCarron, Pearse; Rafuse, Cheryl; Scott, Steven; Lawrence, Janice; Bruce, Meghann R.; Douthwright, Erin; Murphy, Colleen; Reith, Michael; Beach, Daniel G.
Abstract: In July 2018 three dogs died after visiting the Wolastoq (Saint John River) near Fredericton, New Brunswick, in Atlantic Canada. All showed signs of toxicosis, and necropsies revealed non-specific pulmonary edema and multiple microscopic brain hemorrhages. Liquid chromatography– high-resolution mass spectrometry (LC– HRMS) analysis of vomitus and stomach contents as well as water and biota from the mortality sites confirmed the presence of anatoxins (ATXs), a class of potent neurotoxic alkaloids. The highest levels were measured in a dried benthic cyanobacterial mat that two of the dogs had been eating before falling ill and in a vomitus sample collected from one of the dogs. Concentrations of 357 and 785 mg/kg for anatoxin-a and dihydroanatoxin-a, respectively, were measured in the vomitus. Known anatoxin-producing species of Microcoleus were tentatively identified using microscopy and confirmed by 16S rRNA gene sequencing. The ATX synthetase gene, anaC, was detected in the samples and isolates. The pathology and experimental results confirmed the role of ATXs in these dog mortalities. Further research is required to understand drivers for toxic cyanobacteria in the Wolastoq and to develop methodology for assessing occurrence. Graphical abstract: Image 1 Highlights: Cyanobacterial toxins suspected in dog deaths in New Brunswick, Canada, in July 2018. Anatoxins confirmed in samples collected from mortality sites and during necropsies. Morphological and genetic methods used to identify and confirm anatoxin producing species of Microcoleus . Work demonstrates the regional risks presented by benthic cyanobacteria and highlights the need for future research.